Prevalência e fatores associados à desnutrição infantil em Comercinho, Minas Gerais - Sergio William Viana Peixoto (2000)
The aim of this study was to evaluate the nutritional status of children under ten years and compare the nutrition of school children (7-10 years) with malnutrition found in children 0-6 years. Socio-economic, environmental and maternal and child that could be associated with malnutrition. Were evaluated, seeking an explanatory model for this disease in Comercinho, Minas Gerais. In addition, surveys were carried out parasitological study and school attendance. The study was conducted by three pairs of trained local health officials who administered a hands and collected measurements of weight and height of 554 children under ten years. The assessment of nutritional status was made through the construction of the indexes weight / age / sex, weight / age / sex and height / weight / sex, using the package Epi Info and the population of reference of the National Center for Health Statistics (NCHS) . The scale used was not only showing percentiles of malnourished children (below the 3rd percentile), but also those under surveillance or risk of malnutrition (between percentiles 3 and 10) and eutrophic (above the 10th percentile). The prevalence of malnutrition for inidcadores height / age, weight for age and weight / height was 14.5%, 10.0% and 3.1% respectively. In the range of monitoring the prevalence rate was 14.3%, 14.4% and 6.3%. Multivariate logistic regression for height for age and weight for height was 14.5% 10.0% and 3.1% respectively